Job satisfaction among Korean academics: a critical investigation - Kim, Hong Goo (2011)
This study aimed to go beyond a simple descriptive analysis and attempt a critical investigation of phenomena related to job satisfaction. Specifically, the purpose of study was to identify the conditions under which Korean academics work; what aspects they valued in relation to their jobs; how satisfied they were with their jobs; the challenges they faced; how these challenges influenced their job satisfaction; and whether or not there were differences in job satisfaction between particular groups based on demographic and institutional factors.